Conceptual Design of Integrated Chromatographic Processes for the Production of Single (Stereo-)Isomers - García Palacios, Javier; Kaspereit, Malte; Kienle, Achim (Chemical Engineering & Technology, 2009)
A fundamental investigation is performed for integrated processes that combine continuous chromatography and isomerization reactions to produce a single (stereo-)isomer. The focus is on the conceptual design of different process concepts and their theoretical analysis. The investigated process variants include reactor-separator-recycle systems, schemes with side reactors, and chromatographic reactors. As a new option, continuous chromatographic reactors with internally distributed functionalities are suggested. Using parameters of a model system, the performance of the processes is compared based on optimizations of corresponding models. The results reveal the potential and the limits of the different approaches under various conditions. It is found that the suggested new options can allow for significantly enhanced process performance.
Keywords: Chromatography; Enantiomer; Integrated processes; Isomer; Isomerization; Racemization; Reactive separation; Simulated moving bed; True moving bed